2016
DOI: 10.1017/s0007114516001380
|View full text |Cite
|
Sign up to set email alerts
|

Serum betaine is inversely associated with low lean mass mainly in men in a Chinese middle-aged and elderly community-dwelling population

Abstract: Previous studies have demonstrated that betaine supplements increase lean body mass in livestock and improve muscle performance in human beings, but evidence for its effect on human lean mass is limited. Our study assessed the association of circulating betaine with lean mass and its composition in Chinese adults. A community-based study was conducted on 1996 Guangzhou residents (weight/mass: 1381/615) aged 50-75 years between 2008 and 2010. An interviewer-administered questionnaire was used to collect general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Chen et al found that higher serum levels of betaine were associated with lower body fat and better profiles of body fat distribution in Chinese adults aged 40–75 years [34]. Subsequently, they also found higher serum concentrations of betaine were associated with higher lean mass percentage in the same cohort, particular in males [35]. Our previous study also showed that higher serum betaine levels are associated with better body composition in general adults of Newfoundland [36].…”
Section: Discussionmentioning
confidence: 81%
“…Chen et al found that higher serum levels of betaine were associated with lower body fat and better profiles of body fat distribution in Chinese adults aged 40–75 years [34]. Subsequently, they also found higher serum concentrations of betaine were associated with higher lean mass percentage in the same cohort, particular in males [35]. Our previous study also showed that higher serum betaine levels are associated with better body composition in general adults of Newfoundland [36].…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, the trend for some enhancements in work capacity may be particularly useful to coaches working with female athletes in the aesthetic sports who commonly consume very little calories and have high training volumes in the weeks leading up to competition. Finally, given that plasma betaine is inversely associated with the loss of lean mass in middle-aged and older adults [ 54 ], further research is necessary to investigate the effects of betaine supplementation on changes in lean mass in various populations consuming a eucaloric diet.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were inconsistent with the findings from previous cross-sectional studies. Higher serum betaine levels have been observed to be associated with greater lean body mass in male adults who participated in the GNHS study and the CODING (Complex Disease in Newfoundland population: Environment and Genetics) study (20,21) . Humans obtain betaine either from foods that contain betaine or by de novo synthesis of betaine in the body.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the role of betaine in maintaining muscle mass in humans has been a focus of attention. Our previous cross-sectional study found that middle-aged and older men with higher serum betaine levels had a higher percentage of lean mass and a lower likelihood of low lean mass (20) . Consistently, cross-sectional studies from Newfoundland (21) found that higher circulating betaine was associated with greater lean body mass.…”
mentioning
confidence: 90%